Keyboard Fantasies: The Beverly Glenn-Copeland Story - Dixon, Posy (Greenwich Entertainment et Modern Films, 2019)

Serving Each Other: Sharing Economies and Affective Labour in Montréal's Kiki Scene - Tailor, Jesse (Université Carleton, 2019)
Against a tense socio-political backdrop of white supremacy, intensifying pressures of neoliberal fiscal austerity, and queer necropolitics, this thesis addresses performance-based activist forms of place-making for urban-based queer, trans, and gender nonconforming communities of colour. Using participant observation and qualitative interviews with pioneering members of Montréal’s Kiki scene and Ottawa’s emerging Waacking community and interpreting my findings through the theoretical lens of queer of colour theory, critical whiteness studies, queer Latinx performance studies and Chicana feminism, I argue that Kiki subculture, which is maintained by pedagogical processes of ‘each one, teach one’, is instrumental in facilitating i) life-affirming queer kinship bonds, (ii) alternative ways to simultaneously embody and celebrate nonnormative gender expression with Black, Asian, and Latinx identity, iii) non-capitalist economies of sharing, and iv) hopeful strategies of everyday community activism and resilience to appropriative processes during economic insecurity and necropolitical turmoil.

La scène travestie qui est à l’origine du punk à Montréal - Desfossés, Félix B. (Vice, 2017)

Beverly Glenn-Copeland: Inspiring stories and advice from a boundary-breaking musician - Hockin, Johnny (Red Bull Music Academy, 2017)

Queering Discourses of Urban Decline: Representing Montréal's Post-World War II "Lower Main" - Podmore, Julie (Historical Geography, 2015)
In this paper, I examine how urban redevelopment and the regulation of public spaces in Montréal in the 1960s transformed the representations of the Lower Main, the city’s historic red-light and entertainment district. I argue that although the Lower Main had long been central to anti-urban discourses regarding heterosexual prostitution, by the 1960s the increased regulation of the city’s queer and trans populations changed its meaning as a representation of the inner city in decline. A central objective is to use this case study to queer discourses of urban decline by considering how heteronormativity was involved in the construction of the city’s sexual margins in the post-World War II period. A related objective is to call into question the narrative of “decline” itself by providing one example of the opportunities it created for queer place-making.

“We Paved the Way for Whatever Tolerance They Have in Their Lives”: An Interview with Michelle De Ville, “The First Door Bitch in Montreal” - Namaste, Viviane (Trans Activism in Canada: A Reader, 2014)
Centring the voices and experiences of trans identified people as experts on their own lives and agents of change, Trans Activism in Canada opens up a dialogue between scholars and community members in an effort to improve the lives of sex and gender variant people